Realidade virtual como ferramenta pedagógica no ensino da educação física - MONTEIRO, Pedro Antonio Marques da Silva (2019)
Information technologies, communication and electronic media are increasingly present in our lives. Today, most schools use technology to improve the teaching process. However, not all schools have the financial resources to have technological resources. The objective of the study was to present a low cost teaching strategy with virtual reality and to seek the opinion of students about the use of virtual reality in Physical Education classes. The methodological proposal was developed through "pesquisa-ação", in which we put virtual reality glasses during classes, the students experienced the immersive education and answered a questionnaire related to the experience. The sample consisted of 57 students, of both sexes (32 boys and 25 girls, with mean age of 11,9 years), enrolled in the 6th and 7th grades in a private school in Castanhal - Pará. The study was carried out in two classes with the same protocol. To begin with, there was an initial conversation and division of the class into four groups, we set up four virtual reality glasses with the "Google Cardboard" templates, we used the "Human Body VR" program to present the human body and then the groups set up a puzzle of the skeletal system. The experience proposed in the study showed the subjects another vision of Physical Education, in which it is possible to change the daily life of the classes, making them more interactive and differentiated. According to the analyzes carried out, it is observed that virtual reality can be considered an interesting and effective pedagogical tool in Physical Education classes, in terms of the involvement that it exerts, and thus, it presents itself as a tool more like pedagogical resource in Physical Education classes and not an exchange of spaces or methodologies.